Analisis Teknik Pukulan Drum Set pada Lagu Cold Sweat Karya James Brown - Kundiman, Ryan Sean (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the role of rim shoot and ghost notes techniques in shaping dynamic variations in drum set performance in the song "Cold Sweat" by James Brown. As a composition that significantly influenced the development of the funk genre, "Cold Sweat" presents complex rhythmic patterns where the dynamics of drum set playing play a crucial role in creating its distinctive groove. The rim shoot and ghost notes techniques, frequently employed by renowned drummers like Clyde Stubblefield, contribute significantly to the nuances and dynamic variations in the drum performance. Through a qualitative approach with music analysis methods, this research explores how these two techniques are applied in the context of "Cold Sweat," as well as their impact on rhythmic patterns and dynamic interpretation in the drum performance. The study also focuses on the influence of these techniques on the structure and funk feel that defines the music of James Brown. The findings of this research are expected to provide deeper insights into the application of rudimental techniques in funk music and their contribution to the overall quality of drum set performance.